The effectiveness of frenotomy in breastfeeding babies with ankyloglossia (Research, Society and Development, 2024)
Objective: This article seeks to validate the importance of obtaining correct diagnoses of ankyloglossia and to highlight the effectiveness of the frenotomy procedure in breastfeeding newborns with ankyloglossia, emphasizing the significance of breastfeeding and the negative impacts of "tongue-tie" in cases where the defect is neglected. Methodology: This is a qualitative, descriptive, and review study, referring to an integrative literature review with a qualitative approach aimed at analyzing the effectiveness of frenotomy in the breastfeeding of babies with ankyloglossia. Data were collected from the PubMed and Scielo platforms, using the following English descriptors: “Ankyloglossia,” “Oral Frenectomy,” and “Newborn.” The inclusion criteria adopted were articles from the last 5 years, with a direct focus on the topic. Articles that were private, incomplete, literature reviews, or not within the established time frame were excluded.Results: Ten articles obtained after applying the exclusion criteria were listed in table format. Overall, the authors advocate for the performance of the frenotomy procedure when correctly indicated to improve breastfeeding. Final Considerations: Frenotomy is a fundamental procedure for improving the condition of babies with ankyloglossia concerning breastfeeding and swallowing, and it should always be preceded by a correct diagnosis to confirm that the intervention is the appropriate treatment for each specific case.